Atherosclerotic burden in patients with Chronic Kidney Disease on hemodialysis - Velázquez Blanco, Gionnis; Treto Ramírez, Janete; Gutiérrez Gutiérrez, Carlos; Ravelo LLanes, Katia; Rivera Garmendia, Cesia; Cruz Hernández, Pedro (Revista Cubana de Nefrología, 2024)
ABSTRACT Introduction: Chronic Kidney disease is a major problema worldwide and has an increasing epidemic nature with devastating complications. Objetive: Determine the atherosclerotic burden of patients whit chronic Kidney disease in hemodyalisis. Methods: observational, descriptive and cross-sectional study in patients receiving hemodyalisis. Nephrology Service of the Medical-Surgical Research Center, from September 2020 to May 2022. 19 patients were studied taking into account the selection criteria. The variables were obtained from the medical records and an exhaustive questioning and physical examination was performed on each case. Descriptive statistics and inferential statistics were used. Results: 63,2% of patients presented clinical signs of atherosclerosis. The factors associated with atherosclerotic burden were age over 60 years (OR=14,67) and smoking (OR=1,83). Elevated interleukin 6 (OR=19,5), anemia (OR=1,8) and elevated CRP (OR=1,8) were non-traditional risk factors associated whit atherosclerotic burden. Conclusions: Cardiovascular alterations were frequent events in patients with Hemodyalisis. When stratifying patients according to atherosclerotic burden, severe vascular damage predominated.